(In)visible power: A critical policy analysis of edTPA. Issue 2 (3rd April 2021) - Potter, David
Abstract: In less than a decade, Pearson's distribution of the Teacher Performance Assessment (edTPA) has expanded to hundreds of teacher education preparation programs in the United States. Used in more than forty states, the edTPA has become one of the most prevalent forms of high-stakes evaluation for student teachers, with several states requiring candidates to pass edTPA to gain teacher certification. This article examines the history and policies associated with edTPA in arts education. To do this, I examined emerging literature concerning edTPA, with a particular focus on the policy documents released by the Stanford Center for Assessment, Learning, and Equity in conjunction with Pearson. Findings from the study include inconsistencies within the evaluation of fine arts teacher candidates, the absence of arts educators from the development of edTPA, and marginalization by means of forced compliance.